MERANGKUL BAHASA INGGRIS PESANTREN: SEBUAH PENYELIDIKAN NARATIF TENTANG KONSTRUKSI IDENTITAS PESERTA DIDIK - Sani, Hasrul; Zaky Romadhoni, Moh Syahrul (Jurnal TAMBORA, 2025)
World Englishes (WE) recognize diverse English varieties shaped by local cultures, challenging Standard English dominance and empowering global speakers. In Indonesia, pesantren integrates English and Arabic into education, creating Pesantren English, a localized form reflecting cultural values. This aligns with the WE perspective, granting students legitimacy as English speakers and fostering hybrid identities. Narrative inquiry is suitable to explore this linguistic and cultural dynamic. This research explores Pesantren English as a local variety in the expanding circle, examining its role in shaping learners’ identities and cultural expressions. It also aims to guide educators in adopting culturally sensitive teaching methods and recognizing the influence of language teaching on identity construction. The study used narrative inquiry to explore Bilal’s (pseudonym) perception of Pesantren English and its impact on his identity. Data were collected through interviews and a learning journal in June 2022, then analyzed by coding and identifying themes to draw conclusions. Bilal, a student from a pesantren in Tasikmalaya, Indonesia, initially preferred Arabic but grew passionate about English after exposure to Western media. The pesantren enforced strict use of English and Arabic, which helped Bilal improve his language skills through both academic and extracurricular activities. While he valued Standard English and criticized local accents, Bilal viewed English as a tool to spread Islamic values globally without adopting Western culture. He plans to further his studies in English and religion, aiming to use both to promote Islam worldwide.